The legal and economic ramifications of apology in civil dispute resolution process - Saleh, Muhammad Ridhwan; Jahn Kassim, Puteri Nemie (Universitas Muhammadiyyah Yogyakarta, 2017)
In recent years, the role of apology in resolving conflicts and preventing litigation has gained much prominence. Particularly, in civil litigation, apology has the potential to promote negotiations, generate settlements and to some extent mitigate and absolve liability. During the civil dispute resolution process, apology can exists and be used at various stages from the moment the wrong has been committed until the end of the pre-action and pre-trial procedures. Further, apology has been long recognised as an effective tool in the alternative dispute resolution process and a mitigating factor in cases on defamation and contempt of court. Studies have also shown that apology has been efficient in settling family disputes by expediting the reconciliation process. Although some apologies may be protected under the principle of “without prejudice communication” which promotes settlement out of court, it nevertheless, has the effect of being a “double-edged sword” and be used against the party who offered the apology as an evidence to establish guilt. In view of this, several jurisdictions have developed legal mechanisms to counter the negative effects of apologies while at the same time, trying to safeguard the benefits of apologies in promoting early settlements and reducing the number of litigated cases. By doing so, positive consequences whether financially as well as economically, can be seen in relation to the amount of compensation awarded as well as the relevant legal costs incurred at the end of the civil dispute resolution process. As such, this research paper seeks to discuss the ramifications of apology from the legal as well as economic perspectives in relation to civil disputes with the aim of safeguarding the benefits of apologies as well as promoting the use of apologies at various stages of the civil dispute resolution process.